Patulin and Xestoquinol are inhibitors of DNA topoisomerase 1 - Emanuela Tumini; Ralf E. Wellinger; Emilia Herrera-Moyano; Patricia Navarro-Cansino; María García-Rubio; Daniel Salas-Lloret; Alejandro Losada; María J. Muñoz-Alonso; Hélène Gaillard; Rosa Luna; Andrés Aguilera (Proceedings of the National Academy of Sciences, 2025)
DNA topoisomerase 1 (TOP1) is essential for transcription, replication, and repair. Its function relies on two catalytic steps, DNA breakage and rejoining. Inhibitors of the second step prevent DNA rejoining and lead to persistent DNA breaks, acting as topoisomerase poisons, used as anticancer drugs. However, reliable inhibitors of the first step are not available. Here, we provide genetic and molecular evidence supporting that Patulin and, to a lesser extent, Xestoquinol inhibit the first catalytic step of TOP1 in vitro, in yeast and in human cells. Particularly, Patulin prevents the accumulation of TOP1 cleavage complexes caused by the TOP1 poison camptothecin (CPT) in human cells. Moreover, Patulin pretreatment of human or yeast cells reduces DNA damage and the accumulation of DNA breaks upon CPT exposure. Consistent with the protective role of TOP1 against harmful R-loops, Patulin treatment increases R-loops and R-loop-associated cytotoxicity, mimicking the effect of TOP1 silencing. Altogether our findings indicate that Patulin and Xestoquinol are nonpoisoning inhibitors of TOP1, which should potentiate new research approaches in molecular biology and medicine.